Dorsal Striatum Is Compromised by Status Epilepticus Induced in Immature Developing Animal Experimental Model of Mesial Temporal Lobe Epilepsy - Al-Redouan, Azzat; Busch, Aaron; Salaj, Martin; Kubova, Hana; Druga, Rastislav (International journal of molecular sciences, 2025)
This study investigated the striatopallidal complex's involvement in status epilepticus (SE) caused by morphological neurodegenerative changes in a post-natal immature developing brain in a lithium-pilocarpine male Wistar albino rat model of mesial temporal lobe epilepsy. One hundred experimental pups were grouped by age as follows: 12, 15, 18, 21, and 25 days. SE was induced by lithium-pilocarpine. Brain sections were microscopically examined by Fluoro-Jade B fluorescence stain at intervals of 4, 12, 24, and 48 h and 1 week after SE. Each interval was composed of four induced SE pups and a control. Fluoro-Jade B positive neurons in the dorsal striatum (DS) were screened and plotted on stereotaxic rat brain maps. The DS showed consistent neuronal damage in pups aged 18, 21, and 25 days. The peak of the detected damage was observed in pups aged 18 days, and the start of the morphological sequela was observed 12 h post SE. The neuronal damage in the DS was distributed around its periphery, extending medially. The damaged neurons showed intense Fluoro-Jade B staining at the intervals of 12 and 24 h post SE. SE neuronal damage was evidenced in the post-natal developing brain selectively in the DS and was age-dependent with differing morphological sequela.
Keywords: modely nemocí na zvířatech; rat brain; Male; Rats, Wistar; basal ganglia; epilepsy; mužské pohlaví; potkani Wistar; neurony; degenerative neuronal changes; pilokarpin; status epilepticus; krysa rodu Rattus; Pilocarpine; Corpus Striatum; Animals; Status Epilepticus; zvířata; corpus striatum; Neurons; Rats; Disease Models, Animal; Epilepsy, Temporal Lobe; dorsal striatum; seizure; epilepsie temporálního laloku